Pericoronary radiomics texture features associated with hypercholesterolemia on a photon-counting-CT - Kahmann, Jannik; Tharmaseelan, Hishan; Riffel, Philipp; Overhoff, Daniel; Papavassiliu, Theano; Schoenberg, Stefan O.; Froelich, Matthias F.; Ayx, Isabelle (Frontiers in Cardiovascular Medicine, 2023)
Introduction Pericoronary adipose tissue (PCAT) stands in complex bidirectional interaction with the surrounding arteries and is known to be connected to many cardiovascular diseases involving vascular inflammation. PCAT texture may be influenced by other cardiovascular risk factors such as hypercholesterolemia. The recently established photon-counting CT could improve texture analysis and help detect those changes by offering higher spatial resolution and signal-to-noise ratio. Methods In this retrospective, single-center, IRB-approved study, PCAT of the left and right coronary artery was manually segmented and radiomic features were extracted using pyradiomics. The study population consisted of a test collective and a validation collective. The collectives were each divided into two groups defined by the presence or absence of hypercholesterolemia, taken from self-reported conditions and confirmed by medical records. Mean and standard deviation were calculated with Pearson correlation coefficient for correlation of features and visualized as boxplots and heatmaps using R statistics. Random forest feature selection was performed to identify differentiating features between the two groups. 66 patients were enrolled in this study (34 female, mean age 58 years). Results Two radiomics features allowing differentiation between PCAT texture of the groups were identified (p-values between 0.013 and 0.24) and validated. Patients with hypercholesterolemia presented with a greater concentration of high-density values as indicated through analysis of specific texture features as “gldm_HighGrayLevelEmphasis” (23.95 vs. 22.99) and “glrlm_HighGrayLevelRunEmphasis” (24.21 vs. 23.31). Discussion Texture analysis of PCAT allowed differentiation between patients with and without hypercholesterolemia offering a potential imaging biomarker for this specific cardiovascular risk factor.